PENGARUH PENAMBAHAN SERBUK SILIKA PADA MATRIK ALUMINIUM TERHADAP FRACTURE TUOGHNESS - Hendriwan Fahmi; Angga Prima Syokti (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2015)
Fracture toughness is one of the process to determine the resistance of a material to the loading and distributing crack on the specimen. Testing was conducted at the Laboratory Padang Institute of Technology, which this process can be done in several stages - stages that have been planned based on the work steps as follows: aluminum smelting process, followed by the screening process so as to get the size of 200 mesh powder, then the process burning rice husks, followed by filtration to become the size of 200 mesh which is also known as silica powder. From the above steps followed by a mixing process which is used as a means of stirring the materials we create. By using three temperature is 420 ° C, 480 ° C, 540 ° C by using some variation of the volume of 100% aluminum, 90% of the volume of aluminum silica + 10% volume, 80% by volume of aluminum silica + 20% volume, 70% by volume of aluminum + 30% of the volume of silica, 60% by volume of aluminum silica + 40% volume, the added alcohol content of 5% to 70%, then after we did the mixing, then we go with the process of compacting the printing process specimen with a predetermined size and with pressure of 140 MPa, of some of the process then we do the sintering process by using a furnace with a temperature of 420 ºC, 480 ºC, 540 ºC, and then we go to the last process that Fracture toughness testing to determine toughness. So from this test found the best composition is the composition of 80% by volume of aluminum silica + 20% volume with the lowest temperature of 420 ºC and is a composition of 60% by volume of aluminum silica + 40% volume with temperature 480 ºC. of the above results, we can see that the price K1C dependent on energy absorption in the event of breach of the specimen.